New metabolites from the sea snail Mauritia arabica and their antimicrobial activity. (February 2023) - Thi Phuong Linh, Kieu; Trung, Vu Thanh; Phong, Nguyen Viet; Binh, Pham Thanh; Quyen, Vu Thi; Thao, Nguyen Phuong; Thung, Do Cong; Nam, Nguyen Hoai; Van Thanh, Nguyen
Abstract: One new sulfonated oxysterol sodium salt (1 ) and one new sterol (2 ), along with nine known compounds (3 11 ) were isolated from the sea snail Mauritia arabica . Their structures were elucidated by HRESIMS data, NMR spectroscopic analyses, and TDDFT-ECD calculations. Complete NMR data of compounds 3, 4 and 6, and ECD data of 6 are reported for the first time. In bioassays, compounds 1 3, 5 8, and 10 displayed antibacterial activity against Enterococcus faecalis with minimum inhibitory concentration (MIC) values ranging from 32 to 64 μg/mL. In addition, compounds 10 and 6 also showed antifungal activity against C. albicans with MIC values of 32 and 64 μg/mL, respectively. Graphical Abstract: ga1 Highlights: Two new sterols and nine known compounds were isolated from the sea snail Mauritia arabica . Their structures were elucidated by analyses of their HRESIMS, NMR, and ECD spectra. Complete NMR data of three known compounds are reported for the first time. The antimicrobial activity of the isolated compounds was evaluated.